The malaria parasite’s Achilles’ heel: Functionallyrelevant invasion structures (2016)
Malaria parasites have their Achilles’ heel; they are vulnerable in small parts of their relevant molecules where they can be wounded and killed. These are sporozoite and merozoite protein conserved high activity binding peptides (cHABPs), playing a critical role in binding to and invasion of host cells (hepatocytes and erythrocytes, respectively). cHABPs can be modified by specific amino acid replacement, according to previously published physicochemical rules, to produce analogues (mHABPs) having left-handed polyproline II (PPIIL)-like structures which can modulate an immune response due to fitting perfectly into the HLA-DR?1* peptide binding region (PBR) and having an appropriate presentation to the T-cell receptor (TCR). © 2015, Caister Academic Press. All rights reserved.